1999
DOI: 10.2136/sssaj1999.6361841x
|View full text |Cite
|
Sign up to set email alerts
|

Lime‐induced loss of soil organic carbon and effect on aggregate stability

Abstract: We investigated the decline in soil organic C on an Oxic Paleustalf (red earth) as a result of lime application (1.5 t CaCO3 ha−1) in New South Wales, Australia and determined how loss of organic C was related to soil aggregate stability changes. Organic C lost as a result of liming was mainly (up to 84% of total loss) in the form of light fraction (specific gravity <1.8) bound to macroaggregates. With liming, a given level of aggregate stability was achieved at a lower soil organic C level in limed soil (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
4
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 11 publications
5
70
4
3
Order By: Relevance
“…In a recent review, Paradelo et al (2015) concluded that while CaCO 3 addition had a clear positive effect on soil structure, its effect on occluded SOC stocks was uncertain. Positive (Egan et al 2018;Muneer and Oades 1989a, b), non-existent (Paradelo et al 2016) or negative effects (Chan and Heenan 1999) of CaCO 3 -amendment on occluded SOC have indeed been reported. In some instances, it may be difficult to disentangle the integrative effects of agricultural management from the simple effects of CaCO 3 additions.…”
Section: The Effects Of Carbonate On Aggregatesmentioning
confidence: 91%
See 1 more Smart Citation
“…In a recent review, Paradelo et al (2015) concluded that while CaCO 3 addition had a clear positive effect on soil structure, its effect on occluded SOC stocks was uncertain. Positive (Egan et al 2018;Muneer and Oades 1989a, b), non-existent (Paradelo et al 2016) or negative effects (Chan and Heenan 1999) of CaCO 3 -amendment on occluded SOC have indeed been reported. In some instances, it may be difficult to disentangle the integrative effects of agricultural management from the simple effects of CaCO 3 additions.…”
Section: The Effects Of Carbonate On Aggregatesmentioning
confidence: 91%
“…It would thus be expected that the rate of enzymatic decomposition of SOC would increase when Ca 2? saturates the exchange complex (Andersson et al 1999;Chan and Heenan 1999;Thirukkumaran and Morrison 1996). This could be the case in the organic (litter) layer (Minick et al 2017), but is generally not observed in the mineral soil.…”
Section: Ca-soc Interactionsmentioning
confidence: 97%
“…Chan and Heenan [87] suggested that the high microbial biomass present in the organic soil activates rates of decomposition in organic soils treated with lime resulting into reduction in pH value. In addition, clay minerals are in lesser quantity in the organic soil.…”
Section: Effect Of Organic Materialsmentioning
confidence: 99%
“…No entanto, de acordo com Chan & Heenan (1999), Albuquerque et al (2000Albuquerque et al ( , 2003, Costa et al (2004) e Griève et al (2005), o aporte de C e o aumento da atividade microbiana ou do sistema radicular das culturas, resultantes da aplicação de corretivos da acidez do solo, contribuem para a manutenção da estabilidade de agregados, o que poderia ter compensado o efeito dispersante dos corretivos. Assim, os benefícios proporcionados pelos corretivos à produção de matéria seca, durante as duas safras agrícolas (Tabela 2), pode ter minimizado o efeito deletério da dispersão da argila, que teria culminado na redução da macroporosidade (Tabela 3).…”
Section: Resultsunclassified